2001
DOI: 10.1046/j.0028-646x.2001.00282.x
|View full text |Cite
|
Sign up to set email alerts
|

Germination requirements and seedling shade tolerance are not correlated in a Chilean temperate rain forest

Abstract: Summary• In a comparative study of 26 Chilean temperate woody species, the following questions were addressed. Are germination requirements correlated with seedling light requirements? Can germination requirements be used to delimit pioneer and nonpioneer guilds?• To assess dependence of germination on canopy gaps, germination percentages were compared experimentally in gap and understorey environments. Seedling light requirements were quantified by determining the mean light environment naturally occupied by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
74
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(81 citation statements)
references
References 33 publications
5
74
0
2
Order By: Relevance
“…The range size for untransformed percentage of canopy openness from 0.5% to 12.8% is similar to the results found in other studies (Lieberman et al 1995, Figueroa & Lusk 2001, Poorter & Arets 2003, Lusk et al 2006, Moll-Rocek et al 2014. Poorter & Arets (2003) compared 15 studies carried out with different measurement techniques in tropical forests around the world reporting average values of %CO between 0.7 and 4.3% and maxima between 10 and 20%.…”
Section: Discussionsupporting
confidence: 74%
“…The range size for untransformed percentage of canopy openness from 0.5% to 12.8% is similar to the results found in other studies (Lieberman et al 1995, Figueroa & Lusk 2001, Poorter & Arets 2003, Lusk et al 2006, Moll-Rocek et al 2014. Poorter & Arets (2003) compared 15 studies carried out with different measurement techniques in tropical forests around the world reporting average values of %CO between 0.7 and 4.3% and maxima between 10 and 20%.…”
Section: Discussionsupporting
confidence: 74%
“…Although Lomatia hirsuta was also rated as "very intolerant" by Donoso (1989), its presence in old-growth forests, especially those with an overstorey of deciduous Nothofagus obliqua (e.g., Veblen et al 1979), suggests that it tolerates slightly more shade than E. coccineum. This is consistent with data in Figueroa & Lusk (2001), showing that L. hirsuta seedlings on Isla Grande de Chiloé occupied shadier microsites than those of E. coccineum. Gevuina avellana and L. ferruginea have been described as being of intermediate shade tolerance (Donoso 1989), although juveniles of the former can often be found growing in as little as 2 % light, in the shaded understories of old-growth stands (Lusk et al 2008b).…”
Section: Study Speciessupporting
confidence: 82%
“…E. coccineum was described as "very intolerant" of shade by Donoso (1989). Its seedlings were found to have the highest understorey mortality rates of eight rainforest species studied by Lusk (2002), and Figueroa & Lusk (2001) reported that juveniles of E. coccineum were associated with brighter light environments than most other Chilean rainforest evergreens. Although Lomatia hirsuta was also rated as "very intolerant" by Donoso (1989), its presence in old-growth forests, especially those with an overstorey of deciduous Nothofagus obliqua (e.g., Veblen et al 1979), suggests that it tolerates slightly more shade than E. coccineum.…”
Section: Study Speciesmentioning
confidence: 99%
“…1). With only eight species, the seedling bank of this forest is floristically poorer than those of low-altitude temperate rainforests further south (Figueroa & Lusk 2001, Lusk et al 2006, although similar to the seedling bank diversity of some montane temperate forests (Lusk 1995). However, the dominance of C. alba followed by A. punctatum at Coyanmahuida is similar to the composition of other forests in the coast ranges at similar latitudes (Bustamante et al 2005).…”
Section: Discussionmentioning
confidence: 96%
“…Aextoxicon punctatum is considered one of the most shade-tolerant species of the region (Donoso 1989, Figueroa & Lusk 2001, as its seedlings survive in the shadiest understorey microsites of the Valdivian rainforest (Lusk et al 2006). Less is known for certain about the light requirements of C. alba, although this species is also considered to be relatively shade-tolerant (Armesto & Pickett 1985).…”
Section: Discussionmentioning
confidence: 99%